2016
DOI: 10.1590/1518-8345.1176.2812
|View full text |Cite
|
Sign up to set email alerts
|

Integrative review of factors related to the nursing diagnosis nausea during antineoplastic chemotherapy

Abstract: Objective: to identify factors related to the nursing diagnosis nausea among cancer patients undergoing chemotherapy. Method: integrative review conducted in four electronic databases (PUBMED, EMBASE, CINAHL and LILACS) using the key words: neoplasia, antineoplastic agents and nausea. Results: only 30 out of 1,258 papers identified met the inclusion criteria. The most frequent related factors were: being younger than 50 years old, motion sickness, being a woman, emetogenic potential of the chemotherapy, anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Four studies were found that guided the construction of the dimensions of the desired care (9)(10)(11)(12) and six other investigations (13)(14)(15)(16)(17)(18) allowed to extract complementary factors of the care of patients with cancer undergoing chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies were found that guided the construction of the dimensions of the desired care (9)(10)(11)(12) and six other investigations (13)(14)(15)(16)(17)(18) allowed to extract complementary factors of the care of patients with cancer undergoing chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding item 6, the subitem date of the exam was included (expert F). In item 7, 67% of the experts requested the adoption of the main diagnosis in the form of a checklist, culminating in a review of the national literature (14)(15)(16)19) , which resulted in the collection of 45 diagnoses, of which 23 were selected to compose the checklist, and 11 fields were left for free description.…”
Section: Construction and Validation Of An Instrument For Nursing Conmentioning
confidence: 99%
“…A hypothesis that helps to explain the occurrence of unbalanced nutrition ND: less than body requirements in adults/seniors submitted to outpatient antineoplastic chemotherapy is the nausea caused by this modality of cancer treatment, which, in turn, can provoke a feeling of vomiting and aversion to food, thus leading the individual to insufficient intake of nutrients to satisfy his metabolic needs. An integrative review on ND nausea, concluded that young age, female gender, motion sickness, emetic potential of chemotherapy, anxiety, conditioned stimulus and expectation of nausea after treatment are the most frequent factors related to the occurrence of this condition in patients submitted to antineoplastic chemotherapy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…An integrative review was used to identify the format, questionnaires, inclusion and exclusion criteria, literature review, decision on the information to be obtained from the studies selected, interpretation of results, and synthesis of knowledge. 5 This integrative review aims to answer the guiding questions that identify the nursing outcomes concerning comfort during neoplastic chemotherapy. A well-defined strategy was used to search for available literature and to analyze data in relevant research.…”
Section: Methodsmentioning
confidence: 99%
“…The researchers used a standard form to extract information that is important in analyzing the retrieved studies; assessing the collected data; presenting and comparing the results/interpretation; reviewing and synthesizing knowledge; and conclusion. 5,7 The level of evidence in this study was classified by Melnyk and Fineout-Overholt (2010) as follows:…”
Section: Methodsmentioning
confidence: 99%